2010
DOI: 10.5194/bg-7-3095-2010
|View full text |Cite
|
Sign up to set email alerts
|

Methane oxidation in permeable sediments at hydrocarbon seeps in the Santa Barbara Channel, California

Abstract: Abstract.A shallow-water area in the Santa Barbara Channel, California, known collectively as the Coal Oil Point seep field, is one of the largest natural submarine hydrocarbon emission areas in the world. Both gas and oil are seeping constantly through a predominantly sandy seabed into the ocean. This study focused on the methanotrophic activity within the surface sediments (0-15 cm) of the permeable seabed in the so-called Brian Seep area at a water depth of ∼10 m. Detailed investigations of the sediment bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 53 publications
(61 reference statements)
4
22
0
Order By: Relevance
“…In this study, we confirmed the presence of ANME-2 and MOB in Rostocker Seep sediments, which is in accordance with findings by Treude and Ziebis (2010) for the nearby Brian Seep area. In their study the authors suggested that aerobic methane oxidation is active in the sediment surface layer and anaerobic methane oxidation in sediment layers deeper than 5 cm.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In this study, we confirmed the presence of ANME-2 and MOB in Rostocker Seep sediments, which is in accordance with findings by Treude and Ziebis (2010) for the nearby Brian Seep area. In their study the authors suggested that aerobic methane oxidation is active in the sediment surface layer and anaerobic methane oxidation in sediment layers deeper than 5 cm.…”
Section: Discussionsupporting
confidence: 80%
“…The presence of MOB within and below the depth of ANME is surprising, because those two groups should be mutually exclusive given their opposite relationship with oxygen: whereas ANME are inactivated permanently by oxygen (Treude et al, 2005b), MOB depend on oxygen for metabolism. As described by Treude and Ziebis (2010) for Brian Seep, gas bubble migration through permeable sediments can drive pore-water convection that discharges sediment pore water into the ocean (Dando et al, 2000;Haeckel et al, 2007). By continuity, discharged sediment fluid must be replaced, driving a water flow into the sediment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations